Translation, cross-cultural adaptation and content validation of the Canadian Occupational Performance Measure (COPM) in the Ukrainian language - Mangusheva, O.O.; Lazarieva, O.B.; Enemark Larsen, A. (Medicni Perspektivi, 2025)
The study aimed at generating an evidence-informed, culturally adapted and valid translation of the Canadian Occupational Performance Measure (COPM) into the Ukrainian language. Due to increased need for rehabilitation of military personnel during the ongoing war, the secondary purpose of the study was to investigate the feasibility of using the COPM with military servicemen and veterans. The translation procedure followed established guidelines for cross-cultural adaptation of outcome measures with an addition of a Committee Approach to ensure alignment of the translation with the emerging professional terminology in Ukrainian. During pre-testing and field testing, the newly translated Ukrainian version of the COPM was used with 84 occupational therapy clients, 51% of whom were military servicemen and 49% representing general population. Content validity was assessed using Content Validity Index (CVI) with feedback from 20 occupational therapists and 84 clients from six regions of Ukraine through anonymous surveys developed in adherence with the COSMIN methodology for evaluating the content validity of patient-reported outcome measures. As a result, the CVI calculated from anonymous responses of clients of occupational therapy ranged from 0.89 to 0.99 on items associated with relevance, comprehensiveness and comprehensibility of the outcome measure. CVI calculated from responses of occupational therapists was 1.0 for all categories, indicating outstanding content validity. Both occupational therapists and clients of occupational therapy reported the perceived positive impact of the COPM on client-centeredness and occupational focus of occupational therapy services. The new Ukrainian translation of the COPM demonstrated sufficient cultural equivalence, and content validity, making it a valid tool for client-centered and occupation focused occupational therapy practice with both the civilian population and military servicemen. The study describes the first translation and validation of an occupational therapy outcome measure in Ukrainian, contributs to the development of rehabilitation and occupational therapy terminology and the development of occupational therapy in Ukraine. Future studies are necessary for continued psychometric testing of the Ukrainian translation of the COPM with military personnel as well as the general population.